Precede-Proceed Education Model to Health Literacy’s Patient With Hypertension in Pattingalloang Makassar - Irma Andrianys; Kusrini Kadar; Nasrum Massi (Faculty of Nursing, Universitas Hasanuddin, 2017)
Introduction: Health literacy is one of health determinants public health development goals. The aim of this research is to determine the effect of precede-proceed education model on health literacy of patients suffer from hypertension in the working area of Pattingalloang Health Centre Makassar. Method: The research employed quasy-experimental method using nonequivalent control design. The research sample was 40 people. The sample was determined using purposive sampling. Data were obtained using questionnaire and interview then it is analyzed by Mann-Whitney and Spearman statistical test. Results: The results showed that: (1) There was differences in the functional health literacy between hypertension patient group provided with an education and group without education intervention; (2) There was no significant difference in communicative and critical health literacy between group with education intervention and group without education intervention. However, proportion of health literacy of patient with education intervention was better; (3) there was a relation between respondent characteristics, health service access, health information access, and social support that the patient obtained and health literacy. Conclusion: The availability of education to hypertension patients by modifying the precede-proceed model were giving influence to health literacy. This study suggest that involvement of health workers expecially for nurses, in an effort to improve health literacy of patients with counseling, home visite for patients and their families